2016
DOI: 10.1111/jzo.12358
|View full text |Cite
|
Sign up to set email alerts
|

Biogeography of polymorphic phenotypes: Mapping and ecological modelling of coat colour variants in an elusive Neotropical cat, the jaguarundi (Puma yagouaroundi)

Abstract: The jaguarundi Puma yagouaroundi is a small Neotropical cat that presents two main coloration phenotypes (grey/dark vs. reddish). Although these coat colour variants have been known for decades, and historically speculated to be associated with different habitats, their exact geographical distribution has never been mapped. Moreover, their association to different habitats has so far not been tested statistically, so that their ecological relevance with respect to varying environmental features remains unknown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
2
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 37 publications
2
44
2
4
Order By: Relevance
“…To perform in-depth spatial analyses of the two phenotypes (non-melanistic and melanistic), we used the approach proposed by [38] to generate separate potential distribution models for each of them. We used 38 explanatory environmental variables and landscape data: 35 bioclimatic variables obtained from the Worldclim (http://www.worldclim.org) and Climond (http://www.climond.org) databases, a digital elevation model (obtained from the SRTM — http://www2.jpl.nasa.gov/srtm), landscape features (obtained from the ESA GlobCover Project 2009 — http://due.esrin.esa.int/page_globcover.php, and NASA NEO NDVI Modis — http://neo.sci.gsfc.nasa.gov).…”
Section: Methodsmentioning
confidence: 99%
“…To perform in-depth spatial analyses of the two phenotypes (non-melanistic and melanistic), we used the approach proposed by [38] to generate separate potential distribution models for each of them. We used 38 explanatory environmental variables and landscape data: 35 bioclimatic variables obtained from the Worldclim (http://www.worldclim.org) and Climond (http://www.climond.org) databases, a digital elevation model (obtained from the SRTM — http://www2.jpl.nasa.gov/srtm), landscape features (obtained from the ESA GlobCover Project 2009 — http://due.esrin.esa.int/page_globcover.php, and NASA NEO NDVI Modis — http://neo.sci.gsfc.nasa.gov).…”
Section: Methodsmentioning
confidence: 99%
“…The occurrence of the leucistic phenotype observed in the Oriximiná and Caraça populations may represent an opportunity to investigate the possibility of establishing a recessive trait in these populations, such as the near fixation of melanism, another recessive color anomaly, observed in leopards of the Malay Peninsula (Kawanishi et al 2010). On the other hand, the occurrence of different coloration phenotypes in tayras throughout its distribution area, provides an opportunity to investigate possible adaptive advantages of these phenotypes (Silva et al 2016) in relation to the ecological conditions present in their areas of occurrence. …”
Section: Discussionmentioning
confidence: 99%
“…Following Booksmythe et al () I adopted a conservative approach and assigned an effect of 0 to missing effects and an effect opposing the predictions of Gloger's rule when only the sign of the effect was missing. For four effects (four studies) I could not extract a standardised effect due to the nature of the analyses (climate niche modelling, structural equation modelling, canonical correlations; Watson & Hanham, ; Schueler, ; da Silva et al , , ). But since in all cases the authors concluded that the results supported Gloger's rule, I decided to exclude these studies rather than assign them an effect of 0.…”
Section: Support For Gloger's Rulementioning
confidence: 99%